2021
DOI: 10.7573/dic.2020-11-1
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of azoximer bromide (Polyoxidonium®) in patients hospitalized with coronavirus disease (COVID-19): an open-label, multicentre, interventional clinical study

Abstract: A clinical need for aetiotropic coronavirus disease (COVID-19) treatments is required. The immune modulator azoximer bromide (AZB; Polyoxidonium®) is indicated in Russia for use against acute viral infections and during remission. In this study, adults hospitalized with COVID-19 ( n =32) received AZB and standard of care in an open-label, multicentre, interventional study. All patients were symptomatic; 22 had severe disease (National Early Warning Score ≥5) and required mechanical venti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…AZB (12 mg IV once daily for 3 days then IM every other day until D17) has been prescribed to COVID-19 patients in Slovakia and Russia as part of licensed therapy. Phase II studies involving 84 patients were conducted in Russia and historically compared to the control arm of a randomized study in China with matched bio-clinical characteristics 59 , 60 . This protocol was reviewed and approved by an Independent Ethical Committee (Pharmnadzor, REC number 229; 9 April 2020).…”
Section: Immune Adjuvants Used As Cancer Drugs: the Ha And Azb Examplesmentioning
confidence: 99%
“…AZB (12 mg IV once daily for 3 days then IM every other day until D17) has been prescribed to COVID-19 patients in Slovakia and Russia as part of licensed therapy. Phase II studies involving 84 patients were conducted in Russia and historically compared to the control arm of a randomized study in China with matched bio-clinical characteristics 59 , 60 . This protocol was reviewed and approved by an Independent Ethical Committee (Pharmnadzor, REC number 229; 9 April 2020).…”
Section: Immune Adjuvants Used As Cancer Drugs: the Ha And Azb Examplesmentioning
confidence: 99%
“…Initially, reports started to emerge on the prophylactic use of AZB in physicians and healthcare teams working directly with patients, and later in observational studies conducted on patients presenting at hospital (49)(50)(51). Although not made as part of formal studies, these observations indicated possible benefits of AZB in COVID-19 that warranted further investigation.…”
Section: From Research Tool To Medicinementioning
confidence: 99%
“…Although not made as part of formal studies, these observations indicated possible benefits of AZB in COVID-19 that warranted further investigation. An appropriately powered, a well-controlled study was designed and is currently underway (49).…”
Section: From Research Tool To Medicinementioning
confidence: 99%